Pembuatan Briket Tongkol Jagung di desa Sapanang Kabupaten Jeneponto - Iqbal Salim; Yurika Samma Todingan; Abdul Waris; Mursalim; Daniel useng; Febriana Intan Permata Hati; Olly Sanny Hutabarat; Gemala Hardinasinta; Junaedi Muhidong; Muhammad Tahir Sapsal (Abdi Techno, 2026)
Sapanang Village is a village located in Binamu District, Jeneponto Regency, South Sulawesi Province. One of the livelihoods of the people in Sapanang Village is derived from agricultural products, agricultural commodities that are often cultivated, one of which is corn. However, behind the large number of cultivated corn plants, it produces waste called corn cobs. Corn cobs are sometimes simply thrown away by the community, therefore the solution offered regarding the corn cob waste problem is to make corn cob briquettes which are an environmentally friendly solid alternative fuel. The service method used in this work program is to prepare the necessary tools and materials and then socialize how to make corncob briquettes to the public. From the socialization that has been carried out, it can be the answer to the problem regarding corn cob waste that is simply wasted which is used to become something useful, such as being processed into corn cob briquettes as an environmentally friendly, cost-effective and long-lasting fuel. The work program activities that have been implemented have been carried out well and received a positive response.